Dangerous plays - Keene, Carolyn (New York : Aladdin Paperbacks, 2006)
Nancy Drew and her friends find unexpected trouble when they watch a house in London.
008-012.
Accelerated Reader AR
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Dwellings -- Fiction; Mystery and detective stories; London (England) -- Fiction; Mystery fiction